A choice model for mixed decision variables. (September 2018) - Lee, Sanghak; Kim, Hyowon; Kim, Jaehwan; Allenby, Greg M.
Abstract: Consumers increasingly face decisions among discrete and continuous choice alternatives. Deciding what to wear, watch, read and drive often includes alternatives that allow access for a period of time, as opposed to outright ownership of a good. Consumers may also want both, where access provides a wider variety of offerings than possible with ownership, and ownership provides greater assurance of availability. We propose a mixed discrete/continuous utility model for assessing the economic relationship between mixed decision variables. In application to two studies involving on-line music and videos, we find that commonly used models of choice mischaracterize the economic relationship between access and ownership. We explore the degree to which profit maximizing prices are dependent on correctly assessing whether access through subscription services are substitutes or complements to product ownership.